Reducing falls among people living with dementia: A systematic review. (July 2020) - Peek, Kerry; Bryant, Jamie; Carey, Mariko; Dodd, Natalie; Freund, Megan; Lawson, Samuel; Meyer, Claudia
Background: People diagnosed with dementia are at greater risk of falls. Given the increasing incidence of dementia globally, high quality and methodologically rigorous research is needed to inform evidence-based practice initiatives. Aims: To describe the published literature related to describing, reducing or preventing fall incidences for people living with dementia including: (1) trends in the total number of intervention and non-intervention studies between 1997 and 2016; (2) the methodological quality of identified intervention studies; and (3) the effectiveness of interventions designed to reduce the incidence of falls among people living with dementia. Methods: A systematic review of five databases was conducted to identify studies reporting any aspect of falls incidence for people with a diagnosis of dementia. Studies meeting the eligibility criteria were coded as intervention or non-intervention studies. Intervention studies were assessed using Cochrane's Effective Practice and Organisation of Care tool. Data about the effectiveness of interventions meeting Effective Practice and Organisation of Care criteria were extracted. Results: Seventy-two eligible studies were identified; 57 were non-intervention studies, and 15 were intervention studies. The number of published studies increased between 1997 and 2016, peaking in 2013 ( n  = 10). Of the 15 intervention studies, seven studies met Effective Practice and Organisation of Care design criteria with one study rated low risk on all eight Effective Practice and Organisation of Care risk of bias domains. One high-risk exercise-based intervention study demonstrated a significant reduction in falls among people living with dementia. Conclusions: There is currently insufficient evidence to endorse any intervention to reduce falls for people living with dementia in any setting. More high-quality intervention studies are needed.